Monetary policy transmission through islamic and conventional banks in Malaysia - Asbeig, Hussam Idris (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
Monetary policy in Malaysia has been designed to be accommodative and supportive of economic growth with balancing the risk of inflation. Therefore, interest rates have been relatively low during the last decade, and the financing conditions continued to be supportive of economic activities. As the cost of borrowing remains low, the transmission of monetary policy through the traditional channel of interest rate might be diminished. Moreover, the influential presence of the Islamic banks may have further compounded the transmission process of monetary policy via the interest rate channel. This gives more importance to investigating other channels that function through the supply of finance, such as the lending channel. This study investigates the impact of monetary policy changes upon the bank supply of financing as an alternative or complementary mechanism to the traditional money view. In order to disentangle the demand factors from the supply determinants, the study adopts a multiplicative model based on the panel data approach. The study utilises annual data spanning from 2000 through 2011. The bank-level data used in the study covers 24 banks in Malaysia, comprising of 14 conventional banks and 11 Islamic banks. This data is sourced from banks' financial statements, and each micro observation in the data is calculated manually. In particular, the study analyses the impact of the monetary policy measures on the financing behaviour of the Islamic and conventional banks based on their capital strength, liquidity degree and size. The study finds that the changes of monetary policy have no significant impact on the level of financing for either type of banks. Bank specific characteristics namely, size, liquidity and capitalisation are found to be pure independent variables and not sources for any heterogeneous responses to monetary policy actions, which is not supportive of an operative lending channel during the study period in Malaysia.